2006
DOI: 10.1007/s00063-006-1028-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social and Institutional Characteristics on the Appropriateness of Invasive Cardiologic Procedures

Abstract: Social characteristics of patients and institutional characteristics have only a marginal impact on the indication of invasive cardiologic procedures. A trend toward "overdiagnostics" within the group of younger patients has been noticed, even in the case of missing hard medical evidence. A serious deficit of health care research can be found. Consented criteria to assess the appropriateness of medical treatments are missing. More research has to be done in the field of concepts and processes controlling the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…124 Inappropriate percutaneous coronary intervention has been documented in many countries, with prevalence of 4–12% in the US; 55,125 10%–14% in Germany, 126,127 16% in Italy; 128 22% in Israel; 7 20% in Spain; 6 and 3.7% in Korea. 129 In one second-opinion centre in India, 55% of recommended cardiac stents or surgery were deemed inappropriate.…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…124 Inappropriate percutaneous coronary intervention has been documented in many countries, with prevalence of 4–12% in the US; 55,125 10%–14% in Germany, 126,127 16% in Italy; 128 22% in Israel; 7 20% in Spain; 6 and 3.7% in Korea. 129 In one second-opinion centre in India, 55% of recommended cardiac stents or surgery were deemed inappropriate.…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…In Germany, no comparable findings exist. Brause et al (2006), for example, found no substantial differences in the provision of adequate invasive cardiac procedures.…”
Section: Introductionmentioning
confidence: 99%
“… 20–22 Altenhöner studied socioeconomic inequalities in access, utilisation and quality of rehabilitation for patients with CAD in Germany; he established that CR procedures are used less frequently by patients of a lower SES. 23 Conversely, a study by Brause et al 24 found no socioeconomic difference for the appropriateness of a medical indication for coronary interventions in Germany.…”
Section: Introductionmentioning
confidence: 98%